CORPORATE SOCIAL RESPONSIBILITY - Czerwińska, Katarzyna; Krzyżanowska, Krystyna (Acta Scientiarum Polonorum. Oeconomia, 2010)
The assessment of respondents` knowledge standard about Corporate Social Responsibility (CSR) as well as extent of social-responsible companies` recognition and social campaigns made by them have been shown in this article. Moreover reasons and types of social-responsible actions took by Avon company have been presented in this paper. In this study primary and secondary sources and subject literature have been analyzed.